Challenges and solutions in organizing geological field trips for Moroccan secondary school life and earth sciences teachers - Eddif, Aâtika; Selmaoui, Sabah; Chalak, Hanaa; Chakour, Radouan (International Journal of Evaluation and Research in Education (IJERE), 2025)
Teaching and learning earth sciences (ES), notably geology, are conducted across various environments, encompassing the classroom, laboratory, and, most significantly, the field. The field trip is recognized as a key component of practical training and the overall success of the educational process in ES. This paper elucidates the findings of a survey aimed at understanding the challenges faced by Moroccan secondary school teachers of life and earth sciences (LES) in organizing geological field trips. The survey sought to identify the difficulties these teachers encounter and propose potential support mechanisms to mitigate these challenges. The study revealed that teachers often do not arrange geological field trips due to challenges related to administration, personal factors, pedagogy, and didactics. In an effort to address this situation, the study underscores the importance of integrating practical work into teacher training and student education. It also emphasizes the need for the provision of more adequate teaching materials and logistical support to facilitate geological excursions, thereby enriching the appreciation of earth sciences disciplines among both teachers and students. Finally, the establishment of electronic collaboration between local Moroccan universities and secondary schools is recommended as a crucial step towards further improvement.